2013
DOI: 10.3791/51110
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Video Microscopy Measurements of Retinal Blood Flow in Mice

Abstract: Alterations in retinal blood flow can contribute to, or be a consequence of, ocular disease and visual dysfunction. Therefore, quantitation of altered perfusion can aid research into the mechanisms of retinal pathologies. Intravital video microscopy of fluorescent tracers can be used to measure vascular diameters and bloodstream velocities of the retinal vasculature, specifically the arterioles branching from the central retinal artery and of the venules leading into the central retinal vein. Blood flow rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Our value of mean diameter of primary vessels matches that of the in vivo slit lamp biomicroscope (Blair et al, 2016) study and is within the range reported by ex vivo scanning electron microscopy (Ninomiya & Inomata, 2006). However, the diameters reported by intravital microscopy studies (Harris et al, 2013; Lee & Harris, 2008; Z. Wang et al, 2010, 2011; Watts et al, 2013; Wright & Harris, 2008; Wright et al, 2009, 2012; Yadav & Harris, 2011) for the same vessel class are at least a factor of two greater than our values.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Our value of mean diameter of primary vessels matches that of the in vivo slit lamp biomicroscope (Blair et al, 2016) study and is within the range reported by ex vivo scanning electron microscopy (Ninomiya & Inomata, 2006). However, the diameters reported by intravital microscopy studies (Harris et al, 2013; Lee & Harris, 2008; Z. Wang et al, 2010, 2011; Watts et al, 2013; Wright & Harris, 2008; Wright et al, 2009, 2012; Yadav & Harris, 2011) for the same vessel class are at least a factor of two greater than our values.…”
Section: Discussioncontrasting
confidence: 84%
“…While investigating the mouse literature for normative values of diameter, velocity and flow in retinal vessels, we found that there is a paucity of such studies. To the best of our knowledge, we have counted all of fifteen journal papers which measure retinal blood velocity and/or flow in the living mouse eye (Blair et al, 2016; Harris, Watts, & Leskova, 2013; Lee & Harris, 2008; Liu et al, 2017; Muir, Rentería, & Duong, 2012; Z. Wang, Yadav, Leskova, & Harris, 2010, 2011; Watts, Eshaq, Carter, & Harris, 2013; Wright & Harris, 2008; Wright, Messina, & Harris, 2009; Wright, Singh Yadav, McElhatten, & Harris, 2012; Yadav & Harris, 2011; Zawadzki et al, 2015; Zhi et al, 2014, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a protocol similar to that described previously, 13 a solution of fluorescent microspheres (1.9 µm diameter Dragon Green; Bangs Laboratories, Inc, Fishers, IN, USA) was infused (80 µg/rat) to measure blood velocity. Videos were recorded using a 4× objective through a Nikon fluorescein filter, with a video camera exposure time of 10 ms.…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescent MSs (6 × 10 7 ) were injected into each mouse. After systemic injection, the interactions of these MSs with the endothelium of normal and angiogenic vessels of live animals were studied by intravital video microscopy [22].…”
Section: Methodsmentioning
confidence: 99%